MODERATING ROLE OF EXTERNAL FACTORS ON PROJECT FINANCING REQUIREMENTS AND PROJECT DELIVERY DELAY IN THE NIGERIAN CONSTRUCTION INDUSTRY - IBRAHIM , MOHAMMED ADAMU; MOHAMMED, BELLO IDRIS; HAUWA, TIJJANI BAYERO; ASHIRU, MOHAMMED; GARBA, ISAH (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The devastating impact of construction project delivery delays is felt worldwide, with estimated losses running into trillions of dollars annually. As the global demand for infrastructure and construction projects continues to rise, understanding the factors that influence project outcomes is crucial. As such, this study investigated the moderating role of external factors on the relationship between project financing requirements and project delivery delay in the Nigerian construction industry. A survey research design was employed, which collected primary data from 423 construction project stakeholders in Kaduna State and analyzed it using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings of the study revealed that the external factors and project financing requirements exacerbate construction project delivery delays. Furthermore, the study’s external factors were found to moderate the relationship between project financing requirements and project delivery delay by increasing investor or financier’s confidence through reduced volatilities and risk resulting from adequate project planning, illegal development control, proactive risk management and stable regulatory environment. The research recommends that project stakeholders need to reduce or eliminate volatilities and risk caused by the study’s external factors to get favourable financing requirements and expedited project delivery. Policy implications suggested that to foster resilient project delivery with minimal delays, the Nigerian government through the relevant ministries, departments and agencies, should establish a policy framework that takes care of external factors and balances project financing requirements, including affordable collateral and borrowing costs, while encouraging project owners and financial institutions to properly plan projects and adopt proactive risk management strategies that mitigate the impact of the external factors. The study concludes with recommendations for further research on innovative financing models like green bonds or pension funds, and exploring the effectiveness of digital technologies such as building information modelling and blockchain technology in enhancing project planning, financing and delivery.